2022
DOI: 10.1097/mpg.0000000000003443
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL‐37 Correlates With Immune Cell Infiltrate and Fibrosis in Pediatric Autoimmune Liver Diseases

Abstract: Objectives:The activation of innate immune mechanisms is key for chronic liver injury. Interleukin-37 (IL-37) is a profound inhibitor of innate and adaptive immune responses, and its overexpression protects mice from liver inflammation and fibrosis. Here, we characterize the hepatic inflammatory infiltrate and expression of IL-37 in children with autoimmune liver diseases.Methods:We compared the inflammatory microenvironment of the liver in a retrospective cohort of children with primary sclerosing cholangitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Bununla birlikte insan karaciğerinde IL-37 ekspresyonunun normal dokularda çok düşük düzeyde olduğu ve inflamatuar uyarıya yanıt olarak belirgin şekilde arttığı gösterilmiştir (24). Yine insanlarda (çocuk) yapılan araştırmada IL-37'nin ana kaynağı olarak hepatositlerin olabileceği ve bu hücrelerde ekspresse olmasının yanı sıra kolanjiyositler ve portal yollarda bulunan bağışıklık hücrelerinde (yardımcı ve düzenleyici T hücreleri, kupffer ve hepatik yıldız hücreleri) de lokalize olduğunu bildirmişlerdir (25). IL-37'nin farelerde karaciğerin kupffer ve hepatik yıldız hücrelerinde ekspresse olduğu, karaciğer inflamasyonu ve fibrozisi durumunda IL-37 ekspresyonunun arttığı ve bu durumlara karşı karaciğer hücrelerini korumaya çalıştığı ifade edilmiştir (26).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bununla birlikte insan karaciğerinde IL-37 ekspresyonunun normal dokularda çok düşük düzeyde olduğu ve inflamatuar uyarıya yanıt olarak belirgin şekilde arttığı gösterilmiştir (24). Yine insanlarda (çocuk) yapılan araştırmada IL-37'nin ana kaynağı olarak hepatositlerin olabileceği ve bu hücrelerde ekspresse olmasının yanı sıra kolanjiyositler ve portal yollarda bulunan bağışıklık hücrelerinde (yardımcı ve düzenleyici T hücreleri, kupffer ve hepatik yıldız hücreleri) de lokalize olduğunu bildirmişlerdir (25). IL-37'nin farelerde karaciğerin kupffer ve hepatik yıldız hücrelerinde ekspresse olduğu, karaciğer inflamasyonu ve fibrozisi durumunda IL-37 ekspresyonunun arttığı ve bu durumlara karşı karaciğer hücrelerini korumaya çalıştığı ifade edilmiştir (26).…”
Section: Discussionunclassified
“…Bizim çalışmamızda da diğer çalışmalarda (24,25,26,27) olduğu gibi IL-37 immunoreaktivitesinin gebeliğin ikinci ve üçüncü dönemlerinde hepatositlerde pozitif olduğu ancak birinci dönemde immunoreaktivite'nin şekillenmediği görülmüştür. Böylece IL-37'nin gebeliğin ilk dönemlerinde hepatositlerin fonksiyonel gelişimi üzerine katkı sağlamadığını düşündürdü.…”
Section: Discussionunclassified
“… 77 Intracellular IL-37 has been demonstrated to regulate liver fibrosis in two distinct ways: (1) by co-localizing with pSmad3L in cholangiocytes and hepatocytes, directly targeting fibrotic pathways, and (2) by restricting infiltrating lymphocytes, macrophages, and KCs to release proinflammatory and profibrotic cytokines to downregulate liver inflammation and subsequent HSC activation. 78 79 Therefore, IL-37-dependent mechanisms can be targeted to treat inflammatory and fibrotic liver diseases ( Fig. 3 ).…”
Section: Liver Protection By Il-37 In Different Liver Diseasesmentioning
confidence: 99%
“…For example, intranasal administration of IL-37 prevented bleomycin-induced lung fibrosis and inflammation by inhabiting MAPK, PI3K/AKT, and ERK signaling pathways to control cellular processes associated with fibrosis [ 9 , 10 ]. In addition, IL-37 transgenic (IL-37tg) mice relieved autoimmune liver diseases-related fibrosis and immune cell infiltrate via regulating the downstream of Smad3 proteins and TGF-β production [ 11 ]. Of note, current studies have also showed that IL-37tg mice could protect against high fat diet-induced obesity and insulin resistance [ 12 ] by activating AMPK [ 13 ] and by inhibiting mTOR [ 14 ] pathways, which could regulate energy metabolism.…”
Section: Introductionmentioning
confidence: 99%